New Targeted Molecular Therapies for Dedifferentiated Thyroid Cancer. (29th April 2010) - Antonelli, Alessandro; Ferri, Clodoveo; Ferrari, Silvia Martina; Sebastiani, Marco; Colaci, Michele; Ruffilli, Ilaria; Fallahi, Poupak
Abstract : Dedifferentiated thyroid cancer (DeTC) derived from follicular epithelium is often incurable because it does not respond to radioiodine, radiotherapy, or chemotherapy. In cases, RET/PTC rearrangements are found in 30%–40%, RAS mutations in about 10%, and BRAF mutations in around 40%–50%, with no overlap between these mutations results in papillary thyroid cancer, while a higher prevalence of BRAF mutations (up to 70%) has been observed in DeTC. The identification of these activating mutations in DeTC makes this malignancy an excellent model to examine the effect of tyrosine kinase inhibitors (TKIs). Clinical trials with several TKIs targeting RET, and to a lesser extent BRAF, and other TKRs have shown positive results, with about one-third of DeTC showing a reduction in tumor size up to 50%, with the longest treatment duration of approximately three-four years. Angiogenesis inhibitors have also shown promising activity in DeTC. Progress is being made toward effective targeted DeTC therapy. The possibility of testing the sensitivity of primary DeTC cells from each subject to different TKIs could increase the effectiveness of the treatment.